2013
DOI: 10.1007/978-1-4614-7055-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in High Pressure Processing of Foods

Abstract: Briefs in Food, Health, and Nutrition present concise summaries of cutting edge research and practical applications across a wide range of topics related to the fi eld of food science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 334 publications
(359 reference statements)
0
23
0
Order By: Relevance
“…For food subjected to HHP treatments, evaluation of processing parameters on the flavour components is vital to define proper treatment conditions, in order to prevent the loss of unique sensory properties of the seafood and to ensure consumer satisfaction. Recently, studies have investigated the effect of HHP on microorganism inactivation, protein denaturation, enzyme activation and inactivation, and modification of physicochemical properties (e.g., proximate composition, colour, texture and acidity) in squids and other seafood (Gou, Choi, He, & Ahn, 2010;Gou, Xu, Choi, Lee, & Ahn, 2010;Hu et al, 2013;Rastogi & Knorr, 2013;Zhang, Jiao, Lian, Deng, & Zhao, 2015). It is surprising that few studies have reported the changes of volatile compounds in seafood treated at various pressures (Cruz-Romero, Kerry, & Kelly, 2008;Hoover, Metrick, Papineau, Farkas, & Knorr, 1989).…”
Section: Introductionmentioning
confidence: 94%
“…For food subjected to HHP treatments, evaluation of processing parameters on the flavour components is vital to define proper treatment conditions, in order to prevent the loss of unique sensory properties of the seafood and to ensure consumer satisfaction. Recently, studies have investigated the effect of HHP on microorganism inactivation, protein denaturation, enzyme activation and inactivation, and modification of physicochemical properties (e.g., proximate composition, colour, texture and acidity) in squids and other seafood (Gou, Choi, He, & Ahn, 2010;Gou, Xu, Choi, Lee, & Ahn, 2010;Hu et al, 2013;Rastogi & Knorr, 2013;Zhang, Jiao, Lian, Deng, & Zhao, 2015). It is surprising that few studies have reported the changes of volatile compounds in seafood treated at various pressures (Cruz-Romero, Kerry, & Kelly, 2008;Hoover, Metrick, Papineau, Farkas, & Knorr, 1989).…”
Section: Introductionmentioning
confidence: 94%
“…The vessel is filled with a pressure transmitting liquid, e.g., water, and additional water is pumped into the system in order to increase the pressure. During the pressure built-up, the so-called adiabatic heating occurs, i.e., a product-dependent temperature increase caused by compression ( Ragstogi, 2013 ). Thus, HHP units are further equipped with temperature sensors, in order to be able to monitor this adiabatic heating.…”
Section: Overview Of Non-thermal Inactivation Technologiesmentioning
confidence: 99%
“…HPP of Manuka honey has demonstrated the increment total phenolic content (TPC) by 47.16% at 600 MPa for 10 min of time (Fauzi, Farid, & Silva, 2013) with overall good quality yield (Fauzi & Farid, 2015,2016Fauzi et al, 2013;Fauzi, Farid, & Silva, 2014). The perks of applying HPP are that the resultant will show little or no change in the organoleptic and nutritional properties of the product (Rastogi & Knorr, 2013), thus avoiding texture defects, destruction in nutrients, off-flavors, and alteration in color (Gupta, 2012).…”
Section: Introductionmentioning
confidence: 99%